Hubungan Antara Aktivitas Memerah Susu Sapi Dengan Resiko Terjadinya Carpal Tunnel Syndrome Pada Petani Pemerah Susu Sapi Di. Desa Jemowo Kec. Musuk Kab. Boyolali - Marros, Andika Yulian, Sugiyono, S.Fis,M.H. (Kes ) (2017)
Background : Carpal tunnel syndrome (CTS) is an entrapment neuropathy.Sindroma that often happens because the narrowing of the carpal tunnel, either due to edema fascia in hetunnel as well as due to abnormalities in the small bones of the hand, causing pressure on the median nerve in the wrist. the median nerve is different between workers and non-workers. Physiotherapy role is to solve the problem of pain, muscle spasm, decreased muscle strength, tropic change and help the functional limitations in the form of interference with daily activities, especially activities atusethecapabilities of hand gestures and were able to conduct observation grams, educational work areaObjective : To determine herelationship of the activity of milking cows with the incidence of Carpal Tunnel Syndrome in the village Jemowo Musuk District of BoyolaliMethods : Type of research is quantitative, to determine the relationship between the activity of milking the risk factors of Carpal Tunnel Syndrome. Data collection techniques using by way of a specific test to determine complaints Carpal Tunnel Syndrome and questionnaires, the list of questions that will be used by researchers to obtain data from the source directly through the communication process or by asking questions.Results : After processing statistical data using chi square test, which means there is the influence of the relationship between the activity of milking the risk factors of Carpal Tunnel Syndrome obtained p = 0.040 means that Ha Ho accepted or rejected.Conclusion : There is a relationship between the activity of milking the risk factors of Carpal Tunnel Syndrome.